Safety and efficacy of deferiprone for pantothenate kinase-associated neurodegeneration: a randomised, double-blind, controlled trial and an open-label extension study. Issue 7 (July 2019) - Klopstock, Thomas; Tricta, Fernando; Neumayr, Lynne; Karin, Ivan; Zorzi, Giovanna; Fradette, Caroline; Kmieć, Tomasz; Büchner, Boriana; Steele, Hannah E; Horvath, Rita; Chinnery, Patrick F; Basu, Anna; et al.
Summary: Background: Pantothenate kinase-associated neurodegeneration (PKAN) is a rare genetic disorder characterised by progressive generalised dystonia and brain iron accumulation. We assessed whether the iron chelator deferiprone can reduce brain iron and slow disease progression. Methods: We did an 18-month, randomised, double-blind, placebo-controlled trial (TIRCON2012V1), followed by a pre-planned 18-month, open-label extension study, in patients with PKAN in four hospitals in Germany, Italy, England, and the USA. Patients aged 4 years or older with a genetically confirmed diagnosis of PKAN, a total score of at least 3 points on the Barry-Albright Dystonia (BAD) scale, and no evidence of iron deficiency, neutropenia, or abnormal hepatic or renal function, were randomly allocated (2:1) to receive an oral solution of either deferiprone (30 mg/kg per day divided into two equal doses) or placebo for 18 months. Randomisation was done with a centralised computer random number generator and with stratification based on age group at onset of symptoms. Patients were allocated to groups by a randomisation team not masked for study intervention that was independent of the study. Patients, caregivers, and investigators were masked to treatment allocation. Co-primary endpoints were the change from baseline to month 18 in the total score on the BAD scale (which measures severity of dystonia in eight body regions) and the score at month 18 on the Patient Global Impression of Improvement (PGI-I) scale, which is a patient-reported interpretation of symptom improvement. Efficacy analyses were done on all patients who received at least one dose of the study drug and who provided a baseline and at least one post-baseline efficacy assessment. Safety analyses were done for all patients who received at least one dose of the study drug. Patients who completed the randomised trial were eligible to enrol in a single-arm, open-label extension study of another 18 months, in which all participants received deferiprone with the same regimen as the main study. The trial was registered on ClinicalTrials.gov, number NCT01741532, and EudraCT, number 2012-000845-11. Findings: Following a screening of 100 prospective patients, 88 were randomly assigned to the deferiprone group (n=58) or placebo group (n=30) between Dec 13, 2012, and April 21, 2015. Of these, 76 patients completed the study (49 in the deferiprone group and 27 in the placebo group). After 18 months, the BAD score worsened by a mean of 2·48 points (SE 0·63) in patients in the deferiprone group versus 3·99 points (0·82) for patients in the control group (difference −1·51 points, 95% CI −3·19 to 0·16, p=0·076). No subjective change was detected as assessed by the PGI-I scale: mean scores at month 18 were 4·6 points (SE 0·3) for patients in the deferiprone group versus 4·7 points (0·4) for those in the placebo group (p=0·728). In the extension study, patients continuing deferiprone retained a similar rate of disease progression as assessed by the BAD scale (1·9 points [0·5] in the first 18 months vs 1·4 points [0·4] in the second 18 months, p=0·268), whereas progression in patients switching from placebo to deferiprone seemed to slow (4·4 points [1·1] vs 1·4 points [0·9], p=0·021). Patients did not detect a change in their condition after the additional 18 months of treatment as assessed by the PGI-I scale, with mean scores of 4·1 points [0·2] in the deferiprone–deferiprone group and of 4·7 points [0·3] in the placebo–deferiprone group. Deferiprone was well tolerated and adverse events were similar between the treatment groups, except for anaemia, which was seen in 12 (21%) of 58 patients in the deferiprone group, but was not seen in any patients in the placebo group. No patient discontinued therapy because of anaemia, and three discontinued because of moderate neutropenia. There was one death in each group of the extension study and both were secondary to aspiration. Neither of these events was considered related to deferiprone use. Interpretation: Deferiprone was well tolerated, achieved target engagement (lowering of iron in the basal ganglia), and seemed to somewhat slow disease progression at 18 months, although not significantly, as assessed by the BAD scale. These findings were corroborated by the results of an additional 18 months of treatment in the extension study. The subjective PGI-I scale was largely unchanged during both study periods, indicating that might not be an adequate tool for assessment of disease progression in patients with PKAN. Our trial provides the first indication of a decrease in disease progression in patients with neurodegeneration with brain iron accumulation. The extensive information collected and long follow-up of patients in the trial will improve the definition of appropriate endpoints, increase the understanding of the natural history, and thus help to shape the design of future trials in this ultra-orphan disease. Funding: European Commission, US Food and Drug Administration, and ApoPharma Inc.